Technological Characterization and Radon Exhalation Rate of an Olivine Diabase Porphyritic of the Apuiarés Region – CE - Silva, Francisco Diones Oliveira; Neto, Antônio Leal; Soares, Wollker Cunha; Neto, José de Araújo Nogueira; Artur, Antônio Carlos [UNESP]; Mattos, Irani Clezar; Clemente, Igor Magalhães (Universidade Federal do Rio de Janeiro, 2022)
Radon gas (²²²Rn) after cigarette smoking, has been considered the leading cause of lung cancer in the United States, according to studies, 21,000 people die each year from gas inhalation. Thus, it is very important that radon concentrations be known indoors: residences, mines, galleries, among others. The objective of this paper is to present the results of studies on the mineralogical and technological characteristics of a diabase dyke, with the purpose of obtaining characteristics oriented to the application as ornamental rock and for coatings, following the norms of the ABNT and to evaluate the exhalation rate of radon, through the application of methods active detection of radon gas. The dike is located in the municipality of Apuiarés-CE, geologically located in the Borborema Province, NE of Brazil, NE of the Central Ceará Domain, related to meso-cenozoic intrusive and effusive magmatic phenomena. Two blocks of diabase with dimensions of 30x40x30 cm were collected and sent to the laboratory, where the specimens were made for the technological and radiometric tests. The dike is petrographically characterized with Porphyritic Olivine Diabase it corresponds to a rock of dark gray color with variations for black, isotropic structure and porphyritic texture, showing no stains or irregularities in the texture that would compromise the aesthetic standard for use as ornamental rock. The radon exhalation test resulted in 1 ± 3 Bq m-3 and at exhalation rate of radon per unit area (E), 0.001 Bq m-2.h-1. Therefore, in terms of technology characterization and radon exhalation rate ²²²Rn, the Porphyritic Olivine Diabase presents the requirements of use as dimension stones.
Caracterização Tecnológica e Taxa de Exalação de Radônio de um Olivina Diabásio Porfirítico da Região de Apuiarés – CE
Keywords: Dimension stones; Porphyritic olivine diabase; Radon